STRATEGI PASANGAN CALON BUPATI KASMARNI DAN BAGUS SANTOSO MEREDAM ISU NEGATIF DALAM PILKADA DI KABUPATEN BENGKALIS TAHUN 2020 - Zahira "; M.Y. Tiyas Tinov (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2022)
In the implementation of the Pilkada in Bengkalis Regency in 2020 there has been a very tight competition. The pair of candidates for Regent Kasmarni and Bagus Santoso who are often exposed to negative issues about themselves in the implementation of the Pilkada in Bengkalis Regency, starting from the issue of corruption Amril Mukminin (non-active Regent) who is Kasmarni’s husband. The issue of a political dowry to get several political parties and the issue of violations Structured, Systematic and Massive (TSM). However, with the various negative issues, the candidate pair for Regent Kasmarni and Bagus Santoso were able to reduce negative issuess team during the implementation of the Pilkada in Bengkalis Regency in 2020. As for the formulation of the problem in this study, how is the strategy of the candidate pair for Regent Kasmarni and Bagus Santosi to reduce negative issues in the Pilkada in Bengkalis Regency in 2020. This research was conducted with the aim of knowing the strategy of the candidate pair for Regent Kasmarni and Bagus Santoso to reduce negative issues in the Pilkada in Bengkalis Regency in 2020. This research is a descriptive research with a qualitative approach. Data collection techniques used are interviews, and documentation. The data analysis technique used is descriptive and qualitative methods. The results of this study indicate that the candidate pair Kasmarni and Bagus Santoso use strategies to reduce negative issues by using offensive strategies.The couple Kasmarni and Bagus Santoso used an offensive strategy by creating a campaign in every villge with the help of the supporting party and the success team to work together to reduce the issues of coruption, political dowry (political costs) and structured, systematic and massive (TSM) violations that they were exposed to. Defensive strategies attitude to reduce negative issues by approaching the community by going door to door by conveying the vision, mission and programs that are directly related to the needs of the community. Keywords : Bengkalis Regency 2020, Offensive Strategy, Defensive Strategy, Political Dower, Structured, Systematic, Massive (TSM)